2015
DOI: 10.1016/j.cmet.2015.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Histone Methylation Dynamics and Gene Regulation Occur through the Sensing of One-Carbon Metabolism

Abstract: Summary S-adenosylmethionine (SAM) and S-adenosylhomocysteine (SAH) link one-carbon metabolism to methylation status. However it is unknown whether regulation of SAM and SAH by nutrient availability can be directly sensed to alter the kinetics of key histone methylation marks. We provide evidence that the status of methionine metabolism is sufficient to determine levels of histone methylation by modulating SAM and SAH. This dynamic interaction led to rapid changes in H3K4me3, altered gene transcription, provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
457
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 518 publications
(475 citation statements)
references
References 41 publications
15
457
0
3
Order By: Relevance
“…Data were processed in Xcalibur and TraceFinder (Thermo). Parent ion peaks for each acyl-CoA species and their corresponding 13 C 3 15 N 1 -labeled internal standard were integrated to determine relative abundance between samples, whereas ms2 (product ion) data were used to confirm the identity of the parent ion.…”
Section: Determination Of Acyl-coa Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Data were processed in Xcalibur and TraceFinder (Thermo). Parent ion peaks for each acyl-CoA species and their corresponding 13 C 3 15 N 1 -labeled internal standard were integrated to determine relative abundance between samples, whereas ms2 (product ion) data were used to confirm the identity of the parent ion.…”
Section: Determination Of Acyl-coa Speciesmentioning
confidence: 99%
“…In addition, data have emerged recently that support a role of diet in influencing histone modifications in adulthood in a dynamic and reversible manner. For example, levels of histone H3 lysine 4 trimethylation in the liver are sensitive to dietary intake of methionine (13). The ketone body ␤-hydroxybutyrate can also act as a histone deacetylase inhibitor that elevates tissue histone acetylation levels and alters gene expression patterns under ketogenic dietary conditions (14).…”
mentioning
confidence: 99%
“…Indeed, beyond the well-characterized examples of how accumulation of some competitive oncometabolites due to mutations in the metabolic enzymes SDH, FH, and IDH can drive phenotypic changes through epigenetic mechanisms, 21-29 very few studies have assessed whether more transient changes in metabolism without the involvement of oncogenic mutations in Krebs cycle enzymes are also capable of exerting epigenetic effects. 19,[30][31][32] BRCA1-driven accelerated geroncogenesis: A framework for modeling and evaluating aging-driven alterations in the metabolism-epigenetic axis…”
mentioning
confidence: 99%
“…While the expression of MAT1A (Cai et al 1996) is downregulated the levels of both, MAT2A (Cai et al 1996;Liu et al 2011;Tomasi et al 2015;Yang et al 2015) and MAT2B (Martínez-Chantar et al 2003a), gene products are increased. This relates with isozyme switch of MAT I/III to MAT II that leads to lowering of SAM concentration Frau et al 2013) with subsequent dysregulation in methylation of DNA (Frau et al 2012;Tomasi et al 2012) and histones with impact on the gene expression (Mentch et al 2015). The results of the several studies about the effect of the increased MAT2A expression revealed that increased level of MAT II isozyme positively enhances the proliferation of cancer stem cells and may potentiate a cancer development and progression Chen et al 2007).…”
Section: Effect Of Altered Expression Of Mat Genes On Carcinogenesismentioning
confidence: 99%
“…Furthermore, the levels of several essential nutrients may directly affect the flow of metabolites through SAM-cycle and SAM level (Mikol et al 1983;Ghoshal and Farber 1984;Mentch et al 2015) with the impact on the epigenetic changes underlying the carcinogenesis (Mehrmohamadi et al 2016). In addition to methionine, the dietary supply of folic acid, cobalamin and pyridoxal is the solely way for sustaining their levels in human cells.…”
Section: Influence Of Essential Nutrients On Sam Levels and Sam-relatmentioning
confidence: 99%